Cyclic Model for the Asymmetric Conjugate Addition of Organolithiums with Enoates - Nishimura, Katsumi; Fukuyama, Naoshi; Yamashita, Mitsuaki; Sumiyoshi, Takaaki; Yamamoto, Yasutomo; Yamada, Ken-ichi; Tomioka, Kiyoshi (Synthesis, 2015)
The chiral diether ligand controlled asymmetric conjugate addition of organolithiums to nona-2,7-dienedioates preferentially proceeds via the s-cis conformation with coordination of the carbonyl oxygen atom to the lithium to give a lithium E-enolate intermediate. Subsequent intramolecular conjugate addition of the enolate also proceeds via a cyclic transition state involving the lithium and the s-cis-enoate, resulting in trans,trans-trisubstituted cyclohexanes with high enantiomeric excesses and yields.
Keywords: chiral ligand; asymmetric synthesis; organolithiums; conjugate addition; cascade reaction